Setting up a research question for determining the research methodology - Ibrahim, Rahinah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2008)
This paper presents an approach to determine a research question that would enable design researchers to fix their research question as early as possible. It supports Yin’s recommendation that a researcher must determine the research question first because it will guide him or her on the appropriate research approach. The author has developed three main constructs for the formation of a research question—the “how”, the “what” and the “who”—that would lead researchers to develop the subsequent research objectives. They, in turn, will guide the researchers to formulate their sub-research questions, and the appropriate research strategies. The author hopes that this approach will assist novice researchers in unraveling a preliminary design research approach very early on. Hence, it allows the researchers more time to refine their research methodologies upon further literature review.